The Influence of Corporate Reputation And Organizational Support On Organizational Pride And Its Implication Of Organizational Citizenship Behavior - Fiernaningsih, Nilawati (International Journal of Psychosocial Rehabilitation, 2020)
This research aims at analyzing the influence of corporate reputation and organizational support on organizational pride and its implication to organizational citizenship behavior. This research is a quantitative study. This research was conducted in Politeknik negeri Malang with 567 populations and 235 samples consisted of lecturer and academic staff. Sampling technique used was proportionate random sampling. Collected data was processed based on the Descriptive Statistic Analysis Method, Inferential Statistic and Hypothesis Test using PLS program. Based on the result of SEM analysis by using PLS was obtained that there was a significant influence between corporate reputation and organizational support on organizational pride and its implication to organizational citizenship behavior. Politeknik Negeri Malang leader should be able to improve organizational citizenship behavior and institutional reputation through a program which actively contribute to improve social, economic and local community conditions.